A systems model for Political Communication - Paul Vorster (Communicare)
POLITICAL COMMUNICATION as a recently emerged subdiscipline of the Communication Science is rapidly expanding. However, it needs not only to continue its research but also to develop models for further research and theory construction. This paper proposes that in order to get a comprehen- sive view of the field, a holistic perspective is required. The process of political com- munication is described as a systemic ac- tivity. Aspects of a systems approach are discussed and a systems model for political communication is advanced. In this model the major components with its functions are political institutions, the media and the public operating within the qualifying politi- cal culture that characterises the system. It is concluded that a systems approach is, at this stage in the development of Political Communication as a field, preferred to more reductionist approaches.